Search mechanism for data contents based on bloom filter and tree hybrid structure in system wide information management - Zhang, Lizhe; Bai, Zhuoning; Cui, Bohua; Wu, Zhijun (IET communications, 2023)
The system wide information management (SWIM) system infrastructure layer uses information‐centric networking (ICN) to implement the cache routing and sharing of air traffic information data. The SWIM network searches and forwards routes on the basis of content names. The variable length, hierarchical name structure, and routing updates caused by the frequent publication and deletion of content make the implementation of fast name routing lookup algorithms a significant but arduous task. To address this problem, this study designed a name matching mechanism on the basis of the hybrid structure of the Bloom filter and the Tree. Compared with the traditional Bloom filter search scheme, this search mechanism reduces the quantity of Bloom filter insertion entries and reduces the possibility of hash collisions. Compared with the traditional Tree search scheme, the proposed mechanism can effectively solve the problem of numerous memory accesses caused by extremely long name prefixes, improving the query efficiency. In addition, the proposed composite structure is compared with several methods, such as DIPIT and NPT, by analyzing the effects of layering, global delay and search speed. The experimental results show that the proposed structure has a favourable performance in terms of storage overhead and search speed. In this work, we designed a name matching mechanism based on the hybrid structure of Bloom filter and Tree according to the characteristics of the system wide information management (SWIM) system. This search mechanism reduces the number of entries inserted by the Bloom filter and the possibility of hash conflicts. It can well solve the problem of too many memory accesses caused by too long name prefixes, which improves query efficiency. The experimental results show that the structure has good performance in aspect of storage overhead and search speed.